Clinical Relevance of HLA Antibodies in Kidney Transplantation: Recent Data from the Heidelberg Transplant Center and the Collaborative Transplant Study - Caner Süsal; Alexander Fichtner; Burkhard Tönshoff; Arianeb Mehrabi; Martin Zeier; Christian Morath (Journal of Immunology Research)
Herein, we summarize our recent findings from the international Collaborative Transplant Study (CTS) and Heidelberg Transplant Center regarding the role of HLA antibodies in kidney transplantation and their application into the clinical routine. Based on the antibody findings from the CTS serum study, an algorithm was developed in 2006 for the transplantation of high-risk sensitized patients at the Heidelberg Transplant Center which includes seven different pre- and posttransplant measures. Using this algorithm, the number of transplantations could be increased in high-risk presensitized patients and the previously existing impact of antibodies on graft survival could greatly be diminished but not totally eliminated. More recent findings led to the hypothesis that T cell help from a preactivated immune system supports the harmful effects of pretransplant donor-specific HLA antibodies that otherwise disappear in many cases after transplantation without any consequence.